Auditory stimuli from a sensor glove model modulate cortical audiotactile integration - Raquel Metzker Mendes; Rafael Inácio Barbosa; Carlos Ernesto Garrido Salmón; Carlo Rondinoni; Sara Escorsi‐Rosset; Juliana Carla Delsim; Cláudio Henrique Barbieri; Nílton Mazzer (2013)
The purpose of this study was to shed light on cortical audiotactile integration and sensory substitution mechanisms, thought to serve as a basis for the use of a sensor glove in the preservation of the cortical map of the hand after peripheral nerve injuries. Fourteen subjects were selected and randomly assigned either to a training group, trained to replace touch for hearing with the use of a sensor glove, or to a control group, untrained. Training group volunteers had to identify textures just by the sound. In an fMRI experiment, all subjects received three types of stimuli: tactile only, combined audiotactile stimulation, and auditory only. Results indicate that, for trained subjects, a coupling between auditory and somatosensory cortical areas is established through associative areas. Differences in signal correlation between groups point to a pairing mechanism, which, at first, connects functionally the primary auditory and sensory areas (trained subjects). Later, this connection seems to be mediated by associative areas. The training with the sensor glove influences cortical audiotactile integration mechanisms, determining BOLD signal changes in the somatosensory area during auditory stimulation.